2018
DOI: 10.1111/ap.12345
|View full text |Cite
|
Sign up to set email alerts
|

Should Australian Psychology Consider Enhancing Psychotherapeutic Interventions with Psychedelic Drugs? A Call for Research

Abstract: International research is increasingly demonstrating that psychedelic-assisted psychotherapy can enhance psychotherapeutic outcomes and be effective for some treatment-refractory mental illnesses; however, there is an absence of any such research in Australia. A review of psychedelic science has been conducted with a focus on psychedelic-assisted psychotherapy to highlight the degree to which such research is occurring overseas. While some studies are in their early stages and the methods are undergoing contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 77 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…Following a 30-year embargo on psychedelic research (Strauss, Bright, & Williams, 2016), there has been a recent resurgence of scientific interest in the therapeutic and medicinal effects of psychedelic substances, often referred to as the psychedelic renaissance (Bright & Williams, 2018). Contemporary clinical research on higher doses of psychedelics has shown that LSD administered in a supportive setting increases optimism in healthy subjects (Carhart-Harris et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Following a 30-year embargo on psychedelic research (Strauss, Bright, & Williams, 2016), there has been a recent resurgence of scientific interest in the therapeutic and medicinal effects of psychedelic substances, often referred to as the psychedelic renaissance (Bright & Williams, 2018). Contemporary clinical research on higher doses of psychedelics has shown that LSD administered in a supportive setting increases optimism in healthy subjects (Carhart-Harris et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Over recent years, a callto-action has been made in Australian journals to engage in this field of research. [24][25][26][27][28] Some researchers described experiencing resistance when attempting to establish trials of MDMA-AP in Australia, stating a proposed study was 'vetoed by the deputy vice-chancellor' of a university, before the application reached the ethics committee. 27 The current study seeks to assess whether there is bias among psychiatrists, psychologists, general practitioners (GPs) and mental health (MH) researchers, towards MDMA-AP research.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Whereas, to date, most MDMA research has been with PTSD; the BIMA study is the world's first scientific project exploring the potential role for MDMA-assisted psychotherapy as a treatment for alcoholism-or any addiction-and therefore marks an important new direction for MDMA science (Sessa et al, 2019a(Sessa et al, , 2019b. There was also a reinvigorated push from the scientific community to begin psychedelic research in Australia in 2018 (Bright & Williams, 2018), and the country's first experimental trials were ultimately funded in early 2019 (Mannix & Booker, 2019). Lastly, in 2018, entrepreneur Tim Ferriss committed to investing in the world's first psychedelic research center, which opened at the Imperial College London in 2019 (Brodwin, 2019).…”
Section: Advances Within Sciencementioning
confidence: 99%